Cost-effectiveness of prize-based contingency management in methadone maintenance treatment programs - Sindelar, Jody L. (2007)
AIM: To determine if prize-based contingency management (CM), which has been shown to improve treatment outcomes over usual care (UC) alone, is cost-effective. DESIGN: A cost-effectiveness study of a multi-site clinical trial. Data on the outcome measures came from the original effectiveness trial. Cost data were gathered by clinic survey specifically for this cost-effectiveness analysis. SETTING: Six methadone maintenance community clinics participating in the National Drug Abuse Treatment Clinical Trials Network. PARTICIPANTS: Participants were recruited from six methadone maintenance community treatment programs. The study sample consisted of 388 participants: 190 in the UC condition and 198 in the CM condition. Participants were randomized at each site to either the UC or the CM condition based on the presence of stimulants (cocaine, amphetamine or methamphetamine) and opioids in their baseline urine sample. INTERVENTION: Prize-based contingency management added to usual care. MEASUREMENTS: Longest duration of abstinence (LDA), number of stimulant-negative urine samples and costs of treatment. FINDINGS: Compared to usual care, the incremental cost of using prize-based CM to lengthen the LDA by 1 week was $141 [95% confidence interval (CI), $105–$193]. The incremental cost to obtain an additional stimulant-negative urine sample was $70 (95% CI, $53–$117). CONCLUSIONS: By comparing this study to a companion study, we found that adding prize-based CM to usual care may be more cost-effective in methadone maintenance clinics than in counseling-based drug-free clinics.